1999
DOI: 10.1161/01.str.30.4.793
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Potassium Insulin Infusions in the Treatment of Acute Stroke Patients With Mild to Moderate Hyperglycemia

Abstract: Background and Purpose-Hyperglycemia following acute stroke is strongly associated with subsequent mortality and impaired neurological recovery, but it is unknown whether maintenance of euglycemia in the acute phase improves prognosis. Furthermore, the safety of such intervention is not established. Methods-In an explanatory, randomized, controlled trial to test safety, 53 acute (within 24 hours of ictus) stroke patients with mild to moderate hyperglycemia (plasma glucose between 7.0 and 17.0 mmol/L) were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0
9

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(138 citation statements)
references
References 33 publications
2
127
0
9
Order By: Relevance
“…A few exploratory randomised trials showed that glucose-potassium-insulin (GKI) infusions can be safely administered to acute stroke patients with mild to moderate hyperglycaemia producing a physiological but attenuated glucose response to acute stroke, the effectiveness of which remains to be elucidated [25,26]. The large multicentre trial called "GIST-UK trial » (for Glucose Insulin in Stroke Trial) aimed to demonstrate whether treatment with GKI infusions to maintain euglycaemia immediately after the acute event reduces death at 90 days [27].…”
Section: Stroke-associated Hyperglycaemiamentioning
confidence: 99%
“…A few exploratory randomised trials showed that glucose-potassium-insulin (GKI) infusions can be safely administered to acute stroke patients with mild to moderate hyperglycaemia producing a physiological but attenuated glucose response to acute stroke, the effectiveness of which remains to be elucidated [25,26]. The large multicentre trial called "GIST-UK trial » (for Glucose Insulin in Stroke Trial) aimed to demonstrate whether treatment with GKI infusions to maintain euglycaemia immediately after the acute event reduces death at 90 days [27].…”
Section: Stroke-associated Hyperglycaemiamentioning
confidence: 99%
“…Continuous intravenous insulin infusion is the most rational and physiologic method of management of hyperglycemia in ICU. Various studies have demonstrated that this method is safe, effective and flexible [2,[26][27][28]. It is imperative however to monitor blood glucose hourly and titrate the rate.…”
Section: Insulin Therapymentioning
confidence: 99%
“…Insulin can be started either as insulin and glucose infused separately or glucose insulin potassium (GIK) combined solution. While a number of validated and effective protocols for insulin infusion are in use [6,20,27,29], we suggest the following as a simplified method.…”
Section: Regimen For Continuous Insulin Infusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one patient required treatment for symptomatic hypoglycemia. 64 When hyperglycemia is present before an ischemic or anoxic event, neurologic damage is worse. 62 These findings are more consistent in cases of global versus focal ischemia.…”
Section: Neurologymentioning
confidence: 99%